Association of mental disorders and quality of diabetes care-A six-year follow-up study of type 2 diabetes patients in North Karelia, Finland - Nazu, Nazma Akter; Wikström, Katja; Lamidi, Marja-Leena; Lindström, Jaana; Tirkkonen, Hilkka; Rautiainen, Päivi; Laatikainen, Tiina (Diabetes Research and Clinical Practice, 2020)
Aims: To compare the quality of diabetes care among type 2 diabetes patients with and without mental disorders during six-year follow-up in North Karelia, Finland. Methods: All type 2 diabetes patients (n = 10190) were analysed using the electronic health records data from 2011-12 to 2015-16. The diabetes care was evaluated using the measurement activity and the achievement of the treatment targets for HbA1c and LDL. Results: Monitoring of HbA1c and LDL levels improved among all patient groups, except the dementia patients. The proportion of those achieving the HbA1c target declined and those achieving the LDL target improved in all patient groups. Differences in the changes of achievement of the target HbA1c level among patients with dementia and depression were observed when compared with those having only type 2 diabetes. Conclusions: This study highlights the challenge of glucose level management as the age and comorbidities of the patients related to the care and achievements of the treatment targets. Mental disorders that are likely to affect patients' adherence to medication and other treatments should be taken into account and more support for self-care should be provided to such patients. Improvement in the achievement of LDL target address the progress in the prevention of macrovascular complications. (C) 2020 The Authors. Published by Elsevier B.V. Peer reviewed